Composted Materials on Florida Roadsides - Grady L. Miller; Michael S. Harrell; Gerald Kidder; Robert Black (EDIS, 2003)
This fact sheet gives a brief overview of a two-year project conducted by researchers of the University of Florida's Institute of Food and Agricultural Sciences (UF/IFAS) as part of contract WO#7 with the Florida Department of Transportation (FDOT). This document is ENH 872, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 1, 2002.